IMPLEMENTASI PERBANKAN SYARIAH DALAM MENGHADAPI PELUANG DAN TANTANGAN MELALUI UU NO 21 TAHUN 2008 SESUAI FATWA AGAMA DAN NEGARA MENUJU SYARIAH YANG PARIPURNA - Minatul Anggreni; Iza Hanifuddin (MAQASHID, 2021)
Abstract :This study aims to examine the suitability of the fatwa on Islamic banking products. I use a qualitative approach with data sourced from various related books or journals. The development of Islamic financial institutions (LKS) each year has increased significantly, especially in Islamic banking in Indonesia. Based on the fatwa, banks and related parties in this institution apply principles that are in accordance with sharia, namely for depositing funds and financing business activities, or other activities that are declared in accordance with sharia. In addition, the financing provided has many options in accordance with the wishes of Islamic bank customers. In this context, all financing products in Islamic banking must comply with the rules according to syara'. The DSN-MUI fatwa is a stipulation of regulations or regulations that exist in Islamic Banking in Indonesia.Keywords: Fatwa, Opportunity, Islamic Banking, Regulation, Challenge